Creative Person. A.N. Leontiev and Russian Psychology - Vladimir A. Mazilov; Yurii N. Slepko (Lomonosov Moscow State University, 2023)
Background. The study of the contribution of Alexei Nikolaevich Leontiev to the development of Russian psychological science makes it possible to evaluate his outstanding personal qualities, organizational skills, and the talent of a scientist and researcher. Objective. The study is aimed to analyze the role of A.N. Leontiev in the development of Russian psychology as a field of independent scientific knowledge. Methods. The material was obtained in the study of memories on the life and work of A.N. Leontiev. The analysis of theoretical and methodological research on the problems of psychological science was also conducted. Results. The analysis showed that A.N. Leontiev is one of the few psychologists who took responsibility for the development of psychological science in the USSR. This was reflected in the systematic and fundamental organizational activity, in the creation of psychological faculties, scientific journals, training of personnel for psychological institutions. A.N. Leontiev played a significant role in the rapprochement of Soviet and foreign psychology, acquaintance of Soviet psychologists with the research of psychologists abroad. At the same time, A.N. Leontiev managed to make a significant contribution to the solution of theoretical and methodological issues of world psychology. It is asserted that the achievements of A.N. Leontiev in the areas of organizational, scientific, research activities are explained by a combination of personal qualities of a scientist associated with the ability to think strategically, see a systematic solution to problems, and take responsibility. Conclusion. The most significant achievements of A.N. Leontiev are associated with institutionalizing psychology, training psychological personnel, solving fundamental theoretical and methodological problems of Soviet psychology. Despite the vast research on the personality and activity of A.N. Leontiev within Russian psychological science, the task of archival work with sources and materials remains of great importance. There is an urge for broad generalization of the results in the life and creative paths of the scientist, for the spread of materials about A.N. Leontiev among modern young psychologists.